Relatos de la homosexualidad quiteña y cuencana como narrativa subversiva de la heteronormatividad - Velasco Haro, Norma Natasha (2014)
This thesis addresses the significance that homosexuals give their autorelatos, to subvert the heteronormative political order. The overall objective of this dissertation is to identify how the visibility of the gay experience and autorelatos allow transgression of the established order.